Efektivitas Pemberian Terapi Bekam Dan Terapi Pijat Refleksi Terhadap Tekanan Darah Pada Penderita Hipertensi - Rohatami, Oktarina, Arina Maliya, S.Kep, M.Si. Med, Rina Ambarwati, S.Kep, Ns (2015)
Hypertension is one of the non-communicable diseases that is related with reduction number of patients life expectancy, increase in heart disease and the risk of stroke. Many non-pharmacological treatments have been found to help reduce the blood pressure, such as cupping therapy and reflexology therapy. Cupping therapy is able to repair the microcirculation of blood vessels and provide vasodilation effect which can reduce the blood preassure with stable. Whereas reflexology therapy is able to provide a stimulus that is capable to make blood circulate smoothly through the body. This research aim to determine the effectiveness of cupping theraphy and reflexology theraphy related with blood pressure in patients of hypertension. This research method uses pre-experiment design with two design group pre-post test design. Total sample in this study was 60 respondents that divided into 2 groups with 30 persons for cupping therapy and 30 persons for reflexology therapy. Data analysis techniques with paired sample t-test to measure pre-post test blood preassure and difference test between cupping and reflexology use independent sample t-test. From the result of independent sample t-test statistic test showed that p-value 0,018 so Ho is rejected, there are differences in effectiveness for systolic blood pressure and p-value of 0,978, so Ho is accepted there is no difference in effectiveness for diastolic blood pressure. There are differences in effectiveness of systolic blood preassure reduction, but there was no difference in effectiveness of diastolic blood pressure reduction. So it can be concluded that the cupping therapy more effective than reflexology therapy in reducing blood preassure. Cupping therapy and reflexology therapy uis good to be used in alternative therapies to controlling blood pressure to keep stable in patients with hypertension.